2021
DOI: 10.3389/fimmu.2021.746187
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B Cells: Role in Type 1 Diabetes

Abstract: Regulatory B cells (Bregs) have an anti-inflammatory role and can suppress autoimmunity, by employing both cytokine secretion and cell-contact mediated mechanisms. Numerous Breg subsets have been described and have overlapping phenotypes in terms of their immune expression markers or cytokine production. A hallmark feature of Bregs is the secretion of IL-10, although IL-35 and TGFβ−producing B cells have also been identified. To date, few reports have identified an impaired frequency or function of Bregs in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 77 publications
1
7
0
1
Order By: Relevance
“…A decreased proportion of IL-10-producing Bregs with impaired suppressive activity has been recently reported in T1D patients [63 & ,64]. Although it is still unclear how Breg impairment contributes to T1D or whether it is a consequence of chronic inflammation [65], it cannot be excluded that they might also contribute to the lower induction of Tr1 cells.…”
Section: Interleukin-10-producing Type 1 T Regulatory Cells In Type 1...mentioning
confidence: 99%
“…A decreased proportion of IL-10-producing Bregs with impaired suppressive activity has been recently reported in T1D patients [63 & ,64]. Although it is still unclear how Breg impairment contributes to T1D or whether it is a consequence of chronic inflammation [65], it cannot be excluded that they might also contribute to the lower induction of Tr1 cells.…”
Section: Interleukin-10-producing Type 1 T Regulatory Cells In Type 1...mentioning
confidence: 99%
“…Similarly, several paper also reported that peripheral blood circulating Bregs with CD19+CD1d+CD5+ phenotype were increased in patients with tuberculosis ( 51 , 52 ). Interestingly, Breg subsets were found and increased in patients with various autoimmune diseases, including ankylosing spondylitis ( 53 ), primary Sjögren’s syndrome ( 54 ), diabetes mellitus ( 55 ), multiple sclerosis and neuromyelitis optica spectrum disorders ( 56 ), etc., suggesting a close involvement of CD24++CD38++ B cells in the autoimmune pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…39 IL-10, IL-35 and TGF-β producing regulatory B-cells (B reg ) cells are protective in nature and their depletion triggers the switching of naïve B-cells to autoimmune B-cells. 40 In T1D, increased expression of Fas-ligand on IL-10 + B-cells is targeted by CD5 + Fas-L B-cells which causes the apoptosis of the former. Also, PD-L1:PD1 engagement causes increased B reg apoptosis.…”
Section: Changes In the Adaptive Immunity Compartmentmentioning
confidence: 99%
“…T regs control the mitochondrial oxidative phosphorylation (OXPHOS) in T eff cells in prediabetes and T2D and concomitantly support T h 1 or T h 17/T reg cytokine production 39 . IL‐10, IL‐35 and TGF‐β producing regulatory B‐cells (B reg ) cells are protective in nature and their depletion triggers the switching of naïve B‐cells to autoimmune B‐cells 40 . In T1D, increased expression of Fas‐ligand on IL‐10 + B‐cells is targeted by CD5 + Fas‐L B‐cells which causes the apoptosis of the former.…”
Section: Overview Of Alterations Of Immune Responses In Diabetic Indi...mentioning
confidence: 99%
See 1 more Smart Citation